1995
DOI: 10.7326/0003-4819-123-4-199508150-00002
|View full text |Cite
|
Sign up to set email alerts
|

Enterococci Resistant to Multiple Antimicrobial Agents, Including Vancomycin: Establishment of Endemicity in a University Medical Center

Abstract: Vancomycin-resistant enterococci are an important cause of illness and death in the study institution, particularly among organ transplant recipients and other seriously ill persons; they have also become a common intestinal colonizer among hospitalized patients. The diversity of isolates (based on molecular typing studies) suggests that resistant organisms have been introduced from multiple sources. Interventions that effectively lower the overall level of colonization with vancomycin-resistant enterococci mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
294
1
19

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(323 citation statements)
references
References 0 publications
7
294
1
19
Order By: Relevance
“…Published reports support the hypothesis that after VCE are introduced, the rates of colonization and infection increase and vancomycin-resistant enterococci become endemic unless effective control measures are introduced [20,21]. Ostrowski et al [22] in an endemic period on the presence of VRE in a surgical ICU, found 12% colonization and the following risk factors: use of second and third generation cephalosporin, length of hospital stay, plus ICU hospitalization and solid-organ transplants.…”
Section: Discussionmentioning
confidence: 94%
“…Published reports support the hypothesis that after VCE are introduced, the rates of colonization and infection increase and vancomycin-resistant enterococci become endemic unless effective control measures are introduced [20,21]. Ostrowski et al [22] in an endemic period on the presence of VRE in a surgical ICU, found 12% colonization and the following risk factors: use of second and third generation cephalosporin, length of hospital stay, plus ICU hospitalization and solid-organ transplants.…”
Section: Discussionmentioning
confidence: 94%
“…Typically R p ) 1 and R h ( 1, only the product R 0 R p R h must be greater than unity for transmission. Therefore in endemic settings the model predicts that y à p ) y à h , providing one explanation of the observational ¢nding that culturing the hands of HCWs seldom provides pathogen isolates (Morris et al 1995).…”
Section: Transmission Dynamics Of Antibiotic Resistant Pathogens In Hmentioning
confidence: 99%
“…15,16 At present, VRE is a common intestinal colonizer among hospitalized individuals. 5 Vancomycin-resistant E. faecium has been isolated increasingly among patients in intensive care units. 11,12 Furthermore, VRE faecium has also been associated with an increased incidence of bacteremia 17,18 and mortality.…”
Section: Tablementioning
confidence: 99%
“…19 Enterococci readily acquire antibiotic resistant genes and elaborate substances which promote adherence to host tissues, induce tissue damage, and produce inflammatory reactions. 10 Risk factors predicting the acquisition of VRE include the presence of a central venous catheter, neutropenia, 20 intestinal colonization, 5,17 recent or current administration of vancomycin, third generation cephalosporins, metronidazole, clindamycin or imipenem, 5,17,21 severity of underlying disease, 5 7 or more days of hospitalization especially in a surgical ICU, 21 more than 7 days of vancomycin use, 21 and transfer between floors. 21 Most of the patients in the current study were neutropenic and all were severely immuno-compromised.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation